Integrating transaction cost theory with trust and commitment in agricultural supply chain - Nor Afifah Yusof (Human Resource Management Academic Research Society, 2024)
The current population is approximately 7 billion and is expected to grow to 9 billion by mid of this year 2050. It calls for increased and effective mechanisms of agriculture that will feed the growing population, particularly those in developing countries. A large number of farms, identified as more than 80 per cent of the world’s farms, are an important source of food, resilience, and income for the world’s population. However, these farmers bear some challenges, including higher transaction costs, thorny market access, modernisation and pandemic impacts. Small farmers must seek increased productivity and efficiency as a way of improving profits and breaking even; this will also justify the new business strategies required by farmers, especially those in the developing countries market, due to high transaction costs. Two of the most critical factors that have been argued to help in minimising these costs include trust and commitment; however, the impact they have on small farmers has not been the focus of most analytical works. This research aims to bridge this gap in the literature by developing an integrated model that combines trust and commitment theory with transaction cost theory, specifically in the context of small-scale farming in rural areas. This unique framework, based on existing literature, explores how trust and commitment can mitigate transaction costs, improve market entry or continued market presence, and contribute to market sustainability. The research adopts a conceptual research approach to build on existing theory and highlight its practical implications for rural farmers in developing countries, thereby engaging the audience with its real-world relevance. The significant research findings underscore the potential of trust and commitment to not only reduce or eliminate transaction costs but also enhance the flow of information and relationships between small farmers and buyers or suppliers. These findings shed light on the potential for coordinated operations, such as joint procurement of transportation and negotiation of operating expenses, to reduce overall costs and improve market viability. Furthermore, the research emphasisestrust as a relationship type that not only minimisestransaction costs but also aids in managing uncertainties, including those arising from the COVID-19 pandemic that affects small farmers in remote areas. The study concludes that it is possible to enhance the financial viability and sustainability of small-scale farmers through an integrated approach based on trust and commitment theory and transaction cost theories. It suggests future studies to measure these relationships and also find ways of enhancing the flow of information in the market, particularly for small farmers. Further, for institutional improvement and long-run sustainability and profitability, it proposes policies to invest in physical capital, strengthen the market information system and engage in collective activities.